Does Episodic Future Thinking Repair Immediacy Bias at Home and in the Laboratory in Patients With Prediabetes?. Issue 7 (September 2020) - Bickel, Warren K.; Stein, Jeffrey S.; Paluch, Rocco A.; Mellis, Alexandra M.; Athamneh, Liqa N.; Quattrin, Teresa; Greenawald, Mark H.; Bree, Kyle A.; Gatchalian, Kirstin M.; Mastrandrea, Lucy D.; Epstein, Leonard H.
ABSTRACT: Objective: This study aimed to determine if episodic future thinking (EFT) can decrease delay discounting (DD) among adults with prediabetes both in and out of the laboratory. DD measures how much the value of a reinforcer decreases as a function of the delay to receive it. Methods: Adults with prediabetes ( n = 67) completed a three-session study. At session 1, baseline measures (including DD) were collected. At sessions 2 and 3, participants were prompted to engage in either EFT or control episodic thinking (CET) while completing DD and other measures. In addition, between the completion of sessions 2 and 3, participants engaged in EFT or CET at home and completed DD tasks remotely via smartphones or other Internet-connected devices. Results: Results showed significant −1.2759 (−20.24%) reductions in DD in the EFT group compared with a + 0.0287 (+0.46%) DD increase in the CET group ( p = .0149) in the laboratory; and −0.4095 (−8.85%) reduction in DD in the EFT group compared with a + 0.2619 (+5.64%) increase in the CET group ( p = .011) at home. Working memory (measured by Backwards Corsi and Digit Span) was found to moderate the effects of EFT on some measures of DD. EFT did not change measures from the food purchase task or a food ad libitum procedure. Conclusions: Results show that EFT decreases DD in and out of the laboratory and supports the further exploration of EFT as an intervention for prediabetes and related chronic diseases. Clinical Trial Registration: NCT03664726. Abstract : Supplemental digital content is available in the text.